Identification of passion fruit (Passiflora edulis) chromosomes using BAC-FISH - Sader, M. A.; Dias, Y.; Costa, Z. P.; Munhoz, C.; Penha, H. [UNESP]; Bergès, H.; Vieira, M. L.C.; Pedrosa-Harand, Andrea (Springer Nature, 2019)
Passiflora edulis, the yellow passion fruit, is the main crop from the Passiflora genus, which comprises 525 species with its diversity center in South America. Genetic maps and a BAC (bacterial artificial chromosome) genomic library are available, but the nine chromosome pairs of similar size and morphology (2n = 18) hamper chromosome identification, leading to different proposed karyotypes. Thus, the aim of this study was to establish chromosome-specific markers for the yellow passion fruit using single-copy and repetitive sequences as probes in fluorescent in situ hybridizations (FISH) to allow chromosome identification and future integration with whole genome data. Thirty-six BAC clones harboring genes and three retrotransposons (Ty1-copy, Ty3-gypsy, and LINE) were selected. Twelve BACs exhibited a dispersed pattern similar to that revealed by retroelements, and one exhibited subtelomeric distribution. Twelve clones showed unique signals in terminal or subterminal regions of the chromosomes, allowing their genes to be anchored to six chromosome pairs that can be identified with single-copy markers. The markers developed herein will provide an important tool for genomic and evolutionary studies in the Passiflora genus.
Keywords: Bacterial artificial chromosome (BAC); Cytogenetic map; Fluorescent in situ hybridization (FISH); Karyotype; Repetitive DNA sequences; Retrotransposon